A relationship between emotional intelligence and Myer Briggs Big Five personality model. (2015) - Indradevi, R.
Emotional intelligence is the ability to understand the emotions of self and others and react accordingly. Emotional intelligence plays a crucial role in an individual's life. Each individual is unique and personality type of every person differs from one another. Personality types and emotional intelligence are essentially correlated and individuals tend to exhibit differences in their emotional intelligences owing to their personality types. This is a very important concept to be studied especially in present day life to cope up with everyday hurdles. This study focuses on trait EI and Big Five personality traits of individuals. The present study was done to find out the relation between the personality types as per the Myer Briggs Big Five model and the emotional intelligence. The target respondents for this study are students of a well reputed private university in India.